Effects of over-expressing ethylene responsive transcription factor on expression of selected fruit ripening related genes in oil palm (Elaeis guineensis Jacq.) mesocarp - Abd Hadi, Nur Annies (2013)
Fruit development, maturation and ripening are important biological processes unique to plants. During the ripening phase, several physiological and biochemical changes take place through differential expression of various genes that are developmentally regulated. Various approaches have been used to understand the complexity of gene expression and interaction in plants. One of the most important mechanisms of gene expression regulation occurs at the transcriptional level through binding of transcription factors to specific DNA sequences. From a recent study, a transcription factor belonging to the AP2 family members that is highly expressed in mesocarp at the late ripening stage of oil palm fruit designated as EgDREB was isolated and sequenced. The present study aimed to identify genes whose expression is regulated by this transcription factor in the mesocarp tissue of oil palm fruits.Semi-quantitative analysis of EgDREB expression by reverse transcriptase (RT)-PCR showed that it is expressed at different stages of mesocarp development but not at the early ripening stage (12 WAA). EgDREB is also expressed in vegetative tissues including roots and leaves. Thus, 12 WAA mesocarp was selected to study the effects of over-expression of EgDREB in mesocarp tissues on five groups of ripening related cDNAs from oil palm that have been previously identified. Co-bombardment of 12 WAA mesocarp tissue with recombinant vector construct harboring EgDREB and plasmid containing the GFP reporter gene was carried out. Fluorescent detection of GFP microscopically and verification via RT-PCR using GFP-specific primers enabled selection of successfully transformed tissues. Using transient expression assay, it was demonstrated that over-expression of the EgDREB gene in 12 WAA mesocarp tissues results in up-regulation of fruit ripening related genes which are TCTP, MET2a and MET2b. These proteins are categorized under biogenesis of cellular component and protein with binding function or cofactor requirement. More specifically the roles of metallothioneins are in homeostasis of essential metal ions and oxidative stress response. This may suggest that EgDREB is involved in regulating cellular processes related to the roles of these three proteins.